Phenotypic and Molecular detection of Acinetobacter baumannii isolated from patients in Duhok city-Iraq - Abdullah, Zainab H.; Merza, Narmin S. (Science Journal of University of Zakho, 2019)
Acinetobacter baumannii (A. baumannii) is an opportunistic pathogen and one of the most importnat Multidrug resistant microorganisms responsible for a vast array of nosocomial infections. 41 (6.8 %) isolates of A. baumannii were obtained from a total of 603 clinical samples of burn and sputum during the period from March 2018 to February 2019. Twenty two isolates (3.6%) of A. baummanni were recovered from burn infections and nineteen isolates (3.2%) from sputum specimens. Identification and characterization of these isolates was accomplished by the aid of selective media (CHROM agar Acinetobacter) and was finally confirmed by VITEK 2 identification system test. Molecular identification utilizing genus and species-specific primers to detect the 16S rRNA and blaOXA-51 was also applied. The Antibiotic resistance testing was done by the Kirby-Bauer disc diffusion method, 24 .4% of the isolates were Multi-Drug Resistance (MDR), while 65.9% were extensive drug resistance (XDR). All isolates were absolutely resistant (100 %) to most of the antibiotics in use: cefixime, cefotaxime, ceftriaxone, ceftazidime, piperacillin-tazobactam, amoxicillin-tazobactam, while the resistant profile for the other antibiotics can be represented as follows 98 %, 95 %, 90 %, and 83 % For both ciprofloxacin and norfloxacin, gentamycin and meropenem, amikacin, and azithromycin and imipenem, respectively. On the other hand, levofloxacin has a moderate effect on the isolates shown by 51% resistant isolates followed by doxycycline for which 39% of the isolates were resistant. Colistin was the only antimicrobial agent that has an intense effect as the majority of the isolates were sensitive. All the selected isolates of A. baumannii were successfuly produced band corresponded to the intended genes. Accurate and early detection of such bacteria is essential for stimulates effective treatment specifically in intensive care units. Molecular techniques have been successfully applied with high specificity using 16S rRNA and blaOXA-51-like gene as a simple and reliable method to differentiate A. baumannii strains.